Anti-NMDAR encephalitis in a child with long impaired consciousness and persistent antibodies: a case report and mini review - Zhang, Wenhao; Cao, Wenjia; Tao, Wenhan; Wang, Yufei; Tangzhu, Chenchen; Shen, Qinru; Shi, Xulai (Frontiers in Immunology, 2024)
We described a challenging case of anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis in a young girl. Despite enduring months of reduced consciousness with ongoing antibody presence, she ultimately exhibited remarkable improvement within a 5-year follow-up period. Additionally, we conducted a concise review of relevant literature on anti-NMDAR encephalitis, with a specific focus on anti-NMDAR antibodies. Our findings enhance the clinical comprehension of anti-NMDAR encephalitis and offer valuable insights to clinicians for its management.